User centred approach to the design, development and implementation of patient information - Keane, David James (2015)
Clinical pathways define patient journeys with medical devices often utilised to diagnose and treat patients. In the contexts of screening and diagnosis, devices are utilised in the form of investigations and tests. They are utilised to detect preventable medical conditions in otherwise healthy individuals and to determine the cause of symptoms in patients presenting symptoms. Patient experiences of investigations and tests vary depending on the healthcare situation, investigation or test, and requirements, expectations and physical experiences of patients before, during and after investigations and tests. Information can be a valuable resource to inform, support and guide patients, and to contribute to quality patient experiences. However, this can only be achieved if information meets patient needs and preferences. This was the basis of the thesis, which took a user centred approach to the design, development and implementation of patient information.